PROFILE AND CONTINGENT NATURE OF BRAZILIAN SOCIAL SECURITY ACTIVE DEBT BETWEEN 2012 AND 2020 - Almeida dos Santos, Graziele; Lima, Diana Vaz de; Driemeyer Wilbert, Marcelo (Advances in Scientific and Applied Accounting, 2022)
Objective: to analyze the capacity of the Brazilian Government to recover receivables from the active social security debt (DAP). Method: the DAP registration process flow and DAP’s payment probability classification are presented, covering balances, payments, registration time and other details of balances. Next, the recoverability of the DAP is analyzed using descriptive statistics of the data available in the Rendering of Accounts of the President of the Republic, in the General Balance Sheet of the Union (BGU) and on the website of the Attorney General of the National Treasury (PGFN), covering the period from 2012 to 2020, based on the rating classification established by Ordinance No. 293/2017. Results: research findings show that (i) there was an increase in the amount of amounts registered as DAP in the period; (ii) while the DAP stock grew exponentially in relation to the gross domestic product (GDP), the recovery of these values ​​remained relatively constant; (iii) 64.8% of the amounts recorded in the period corresponded to irrecoverable credits or those with a low probability of recovery. Therefore, the recoverability of receivables arising from the active Brazilian social security debt is low, evidencing the contingent nature of these amounts. Contributions: the study confirms the findings in the literature on the low level of recovery of receivables and their doubtful accumulation in the public sector financial statements, and warns about the discrepancies observed in the official databases that deal with the active Brazilian social security debt.